Estudio de la señal respiratoria derivada del ECG en función de la posición en sujetos sanos (2020)
Nowadays, the analysis of biomedical signals has become an important source of information in the health sector by providing relevant data on the different systems that constitute the human body. One of the most studied signals is the electric performance of the heart obtained by electrocardiography. Furthermore, these signals contain information related to the respiratory activity. The main objective of this project is to characterize the respiratory signal from the electrocardiographic signal, considering the position of the subject sitting and supine. Different algorithms have been developed to determine the characteristic parameters of the electrocardiographic signal for the identification of the QRS complex. Methods related to the area, the slopes and the angles of the complex QRS have been implemented to obtain the respiratory signal from the ECG. The signals from leads I, II, III and Chest have been analyzed and compared with the respiratory volume signal. Based on the correlation between the different signals, their similarity to the respiratory signal has been determined as a function of the position of the subject. Taking into consideration the results obtained, we observe that Chest lead presents the highest similarity to the respiratory signal for the three methods.